ANALISIS CIRI SASTRA KONTEMPORER DALAM NOVEL"ZIARAH" KARYA IWAN SIMATUPANG - Muhammad Ridho; Liza Septa Wilyanti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the analysis of the novel "Ziarah" by Iwan Simatupang based on the features of contemporary literature. This study uses a qualitative descriptive approach with descriptive analysis methods. Data collection techniques used in this study were library techniques, listening, and taking notes. The results show that the analysis of contemporary literary features in Iwan Simatupang's Ziarah novel consists of anti-character, anti-plot, mysterious and magical atmosphere, anti-logic, absurd or all-odd, as well as isolated and complex. Thus, it can be concluded that almost all contemporary features contained in this Ziarah novel are only transcendental Sufistic or mystical and tend to return to local traditions or colors that are not present in this novel.